PENERAPAN MODEL VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP SIKAP SOSIAL SISWA PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Vira, Alma; Ananda, Rizki; Syahrul Rizal, Muhammad; Hana Pebriana, Putri; Fitra Surya, Yenni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the lack of positive social attitudes among students during science learning in Grade IV at UPT SDN 011 Langgini, Bangkinang District, Kampar Regency. One solution to address this issue is the use of the Value Clarification Technique (VCT) model. This study aims to determine the planning and implementation of the Value Clarification Technique (VCT) model in improving students' social attitudes in science learning. The research methodology employed is Classroom Action Research (CAR), conducted in two cycles, each consisting of two meetings and four stages: planning, implementation, observation, and reflection. The study was carried out from May to June 2024, with a sample of 14 fourth-grade students, comprising 10 boys and 4 girls. Data collection techniques included documentation and observation. The social attitudes of students before receiving the intervention were 21.42%. After the intervention in the first cycle, it increased to 50%, and in the second cycle, it further increased to 85.71%. Based on the research findings, it can be concluded that the Value Clarification Technique (VCT) model can improve students' social attitudes in science learning at UPT SDN 011 Langgini.